Moving Boundary Simulation of Iron-Zinc Sacrificial Corrosion under Dynamic Electrolyte Thickness Based on Real-Time Monitoring Data - SAEEDIKHANIGERAEI, MOHSEN (ELECTROCHEMICAL SOCIETY, 2020)
10.1149/1945-7111/ ab7368